Performance Evaluation of BD Phoenix NMIC-413 Antimicrobial Susceptibility Testing Panel for Imipenem, Meropenem, and Ertapenem Against Clinical Carbapenem-Resistant and Carbapenem-Susceptible Enterobacterales - Zhang, Jingjia; Jia, Peiyao; Zhu, Ying; Zhang, Ge; Xu, Yingchun; Yang, Qiwen (Frontiers in Medicine, 2021)
Purpose: The infection of carbapenem-resistant Enterobacterales (CRE) has become a major clinical and healthcare problem worldwide. The screening methods of CRE have been extensively developed but still need improving [e.g., tests with accurate and simple minimum inhibitory (MICs)]. In this study, the performance of the BD Phoenix NMIC-413 AST panel was evaluated against clinical CRE and carbapenem-susceptible Enterobacterales (CSE) in China. The panel was first evaluated in the Chinese clinical lab. Methods: Antimicrobial susceptibility testing of 303 clinical Enterobacterales isolates were conducted by broth microdilution (BMD), Phoenix NMIC-413 AST panel, and disk diffusion method for imipenem, ertapenem, and meropenem. Considering BMD is a gold standard, essential agreement (EA), categorical agreement (CA), minor error (MIE), major error (ME), and very major error (VME) were determined according to CLSI guidelines. CA and EA > 90%, ME <3%, and VME <1.5% were considered as acceptable criteria. Polymerase chain reaction and sanger sequencing were performed to determine the β-lactamase genotypes of CRE isolates. Results: Three hundred and three isolates included 195 CREs and 108 CSEs were enrolled according to the BMD-MIC values of three carbapenems. Tested CREs showing 100 blaKPC−2-positive organisms, 31 blaIMP-positive organisms, 28 blaNDM-positive organisms, 5 blaVIM-positive organisms, 2 both blaIMP and blaVIM-positive organisms, 2 blaOXA−48-positive organisms, and 27 isolates without carbapenemase genes. For the Phoenix NMIC-413 method, CA and EA rates >93%, MIE rates <5%, ME rates <1.75%, and VME rates were 0%, across the three drugs. For the disk diffusion method, the CA rates for three drugs were all >93%, while the MIE and ME rates were all <5 and <3%, respectively. VME rate was 3.28% for imipenem, exceeded the cut-off value specified by CLSI M52, 0 and 0.56% for ertapenem and meropenem, separately. Conclusion: Based on the genomic data, the detection of CRE and CSE was more reliable using the BD Phoenix NMIC-413 panel compared to the BMD and disk approaches. Therefore, our study supports the use of BD Phoenix NMIC-413 panel as a suitable alternative to BMD for the detection of carbapenem resistant isolates in a clinical setting.